The current status of stem cell‐based therapies during ex vivo graft perfusion: An integrated review of four organs. Issue 12 (25th August 2022) - Luijmes, Stefan H.; Verstegen, Monique M. A.; Hoogduijn, Martin J.; Seghers, Leonard; Minnee, Robert C.; Mahtab, Edris A. F.; Taverne, Yannick J. H. J.; Reinders, Marlies E. J.; van der Laan, Luc J. W.; de Jonge, Jeroen
Abstract : The use of extended criteria donor grafts is a promising strategy to increase the number of organ transplantations and reduce waitlist mortality. However, these organs are often compromised and/or damaged, are more susceptible to preservation injury, and are at risk for developing post‐transplant complications. Ex vivo organ perfusion is a novel technology to preserve donor organs while providing oxygen and nutrients at distinct perfusion temperatures. This preservation method allows to resuscitate grafts and optimize function with therapeutic interventions prior to solid organ transplantation. Stem cell‐based therapies are increasingly explored for their ability to promote regeneration and reduce the inflammatory response associated with in vivo reperfusion. The aim of this review is to describe the current state of stem cell‐based therapies during ex vivo organ perfusion for the kidney, liver, lung, and heart. We discuss different strategies, including type of cells, route of administration, mechanisms of action, efficacy, and safety. The progress made within lung transplantation justifies the initiation of clinical trials, whereas more research is likely required for the kidney, liver, and heart to progress into clinical application. We emphasize the need for standardization of methodology to increase comparability between future (clinical) studies. Abstract : This mini‐review of pre‐clinical studies describes the current landscape of stem‐cell based therapies administered during ex vivo organ perfusion and urges the initiation of clinical trials.